Reasons for taking up postgraduate education by nurses - Bogusz, Renata; Majchrowska, Anita (Nursing in the 21st Century, 2012)
REASONS FOR TAKING UP POSTGRADUATE EDUCATION BY NURSESIntroduction. The specificity of the position of a nurse requires regular updates of one’s knowledge and skills. Furthermore, the Nursing and Midwifery Act stipulates that in-service postgraduate training available in a variety of forms is both a duty and a right of employees. Unfortunately, there exist a number of factors which hinder professional development among members of the two groups. In view of the above, it is still worth considering what makes nurses want to improve their skills.Aim. The aim of the research was to identify the factors which motivate nurses to attend postgraduate training courses.Material and methods. An auditorium questionnaire survey was conducted in 2012 among 102 nurses who participated in professional training delivered by the Centre of Postgraduate Education, Medical University of Lublin.Results. The respondents assessed nurses as highly interested in postgraduate education. Specialization and specialist training were regarded as most demanded. The surveyed mentioned the following key factors which make nurses undertake extra training: people’s own belief that they should expand and update their knowledge, enhanced job prospects and need for continuous learning due to the development of medical sciences. The factors which are thought to discourage nurses from improving their qualifications include: insufficient financial resources, lack of institutional financial support, little chance of financial reward afterwards, lack of training leave as well as unfavourable system of work which makes it difficult to attend classes.Conclusions. The respondents discerned the need to improve professional skills and were convinced that medical knowledge requires regular updates. Still, they pointed to systemic impediments which often discourage nurses from undertaking postgraduate education.